Fat and Water Contents of The Muscle and Gonad of Otolithus argenteus in Relation to Gonad Growth - VINAYAK, V; NEELAKANTAN, B (Fishery Technology, 2017)
Fat and water contents of the muscles and gonads in relation to gonad growth in Otolithus argentes from Karwar are reported. Water content showed an inverse relationship to lipid in both the sexes. Variation in somatic body weight was found associated with the fluctuations in Jjpid contents